Expanding the Pseudomonas diversity of the wheat rhizosphere: four novel species antagonizing fungal phytopathogens and with plant-beneficial properties - Poli, Noémie; Keel, Christoph Joseph; Garrido-Sanz, Daniel (Frontiers in Microbiology, 2024)
Plant-beneficial Pseudomonas bacteria hold the potential to be used as inoculants in agriculture to promote plant growth and health through various mechanisms. The discovery of new strains tailored to specific agricultural needs remains an open area of research. In this study, we report the isolation and characterization of four novel Pseudomonas species associated with the wheat rhizosphere. Comparative genomic analysis with all available Pseudomonas type strains revealed species-level differences, substantiated by both digital DNA-DNA hybridization and average nucleotide identity, underscoring their status as novel species. This was further validated by the phenotypic differences observed when compared to their closest relatives. Three of the novel species belong to the P. fluorescens species complex, with two representing a novel lineage in the Pseudomonas phylogeny. Functional genome annotation revealed the presence of specific features contributing to rhizosphere colonization, including flagella and components for biofilm formation. The novel species have the genetic potential to solubilize nutrients by acidifying the environment, releasing alkaline phosphatases and their metabolism of nitrogen species, indicating potential as biofertilizers. Additionally, the novel species possess traits that may facilitate direct promotion of plant growth through the modulation of the plant hormone balance, including the ACC deaminase enzyme and auxin metabolism. The presence of biosynthetic clusters for toxins such as hydrogen cyanide and non-ribosomal peptides suggests their ability to compete with other microorganisms, including plant pathogens. Direct inoculation of wheat roots significantly enhanced plant growth, with two strains doubling shoot biomass. Three of the strains effectively antagonized fungal phytopathogens (Thielaviopsis basicola, Fusarium oxysporum, and Botrytis cinerea), demonstrating their potential as biocontrol agents. Based on the observed genetic and phenotypic differences from closely related species, we propose the following names for the four novel species: Pseudomonas grandcourensis sp. nov., type strain DGS24 T (=DSM 117501 T =CECT 31011 T ), Pseudomonas purpurea sp. nov., type strain DGS26 T (=DSM 117502 T =CECT 31012 T ), Pseudomonas helvetica sp. nov., type strain DGS28 T (=DSM 117503 T =CECT 31013 T ) and Pseudomonas aestiva sp. nov., type strain DGS32 T (=DSM 117504 T =CECT 31014 T ).